INNOVATIVE APPROACHES TO THE DEVELOPMENT OF FOREIGN ECONOMICACTIVITIES OF AN ENTERPRISE - ABDULLAIEVA, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores contemporary innovative approaches to enhancing the foreign economic activity (FEA) of enterprises in the context of globalization, technological development, and digital transformation of business processes. Special attention is paid to the integration of digital technologies, such as CRM and ERP systems, automated supply chain management, e-commerce platforms, and data analytics tools that support strategic decision-making in international markets. The study emphasizes the growing importance of cross-cultural communication, localization strategies, and the use of international marketing practices tailored to the characteristics of foreign target markets.A comparative analysis of traditional and innovative models of foreign economic activity has been conducted, which reveals the advantages of innovation-oriented strategies in increasing operational efficiency, risk management, and overall competitiveness. The article also addresses the impact of digital infrastructure development and international regulatory frameworks on FEA, highlighting the need for adaptive, flexible business models.Furthermore, recommendations are proposed for the practical implementation of innovative tools in enterprises' external economic operations, taking into account current global challenges such as geopolitical instability, technological shifts, and sustainability trends. The findings of the research are intended to be useful for business owners, export-import managers, and policymakers engaged in international trade and cooperation.
Keywords: foreign economic activity; innovation; digitalization; international marketing; competitiveness